PENGARUH MINUMAN ENERGI DAN SUSU FERMENTASI TERHADAP PELEPASAN ION FOSFAT DAN FLUOR RESIN KOMPOSIT BIOAKTIF - Irpansyah Irpansyah; Sherli Diana; Aulia Azizah (Dentin, 2020)
ABSTRACTBackground: Bioactive composite resin is a restoration material which has the ability to release calcium, phosphate, and fluorine ions. Bioactive composites release the ion at an acidic pH. The release of ions causes reduced activity of protease enzymes such as metalloproteinases (MMPs) and cathepsins which play a role in collagen degradation. This enzyme is one of the causes of decreasing the life of the bioactive composite resin with dentin. Purpose: The purpose of this study was to determine the effect of energy drinks and fermented milk on the release levels of phosphate ions and fluorine ions of bioactive composite resins. Methods: The bioactive composite resin specimens (ACTIVATM BioACTIVE-Restorative / USA) with a diameter of 15mm and 1mm thick (ISO 4149) were divided into 3 immersion groups. The release of phosphate ions was measured using a UV-VIS spectrophotometer and the release of fluorine ions was measured using a Lutron pH meter. Results: The largest release of phosphate ions occurred in the energy drink immersion group and the largest release of fluorine ions occurred in the fermented milk immersion group. Conclusion: The immersion group of energy drinks and fermented milk had an effect on the release of phosphate ions and fluorine ionsKeywords : Bioactive Composite Resin, Energy Drink, Fermented Milk, Fluorine Ion, Phosphate IonABSTRAK      Latar Belakang: Resin komposit bioaktif merupakan bahan restorasi yang memiliki kemampuan melepaskan ion kalsium, ion fosfat, dan ion fluor. Komposit bioaktif mengeluarkan ion pada pH yang asam. Pelepasan ion menyebabkan berkurangnya aktivitas enzim protease seperti metalloproteinases (MMPs) dan cathepsin yang berperan dalam degradasi kolagen. Enzim tersebut merupakan salah satu penyebab penurunan usia ikatan resin komposit bioakif dengan dentin. Tujuan: Tujuan penelitian ini adalah untuk mengetahui pengaruh minuman energi dan susu fermentasi terhadap kadar pelepasan ion fosfat dan ion fluor resin komposit bioaktif. Metode: Spesimen resin komposit bioaktif (ACTIVATM BioACTIVE-Restorative/USA) diameter 15mm dan tebal 1mm (ISO 4149) yang dibagi menjadi 3 kelompok perendaman. Pelepasan ion fosfat diukur menggunakan spektrofotometer UV-VIS dan pelepasan ion fluor diukur menggunakan pH meter Lutron. Hasil: Pelepasan ion fosfat terbesar terjadi pada kelompok perendaman minuman energi dan pelepasan ion fluor terbesar terjadi pada kelompok perendaman susu fermentasi. Kesimpulan: Kelompok perendaman minuman energi dan susu fermentasi memiliki pengaruh terhadap pelepasan ion fosfat dan ion fluor.Kata kunci: Ion Fluor, Ion Fosfat, Minuman Energi, Resin Komposit bioaktif, Susu Fermentasi.